Effect of Solvent Polarity and Protein Models on Anti-Inflammatory Properties of Kratom (Mitragyna speciosa) Leaf Extract (Journal of Tropical Pharmacy and Chemistry, 2025)
Protein denaturation plays an important role in the inflammatory process, and inhibition of this mechanism is widely used as an indicator of anti-inflammatory potential in vitro. This study aimed to investigates the effect of solvent polarity and protein models on the anti-inflammatory activity of Mitragyna speciosa (kratom) leaf extract using albumin denaturation assays with egg albumin and bovine serum albumin (BSA). Extracts were prepared using solvents of different polarities—n-hexane (non-polar), ethyl acetate (semi-polar), and ethanol (polar)—and tested at concentrations of 200, 500, and 1000 ppm. The results showed that solvent polarity and assay model strongly influenced inhibitory activity. In the egg albumin model, the highest inhibition was observed in the ethyl acetate extract at 1000 ppm (45.35%) with an IC₅₀ of 1232.5 ppm, followed by n-hexane extract (IC₅₀ = 1966.7 ppm). Ethanol extract exhibited comparatively lower inhibition (maximum 27.84%; IC₅₀ = 2214.7 ppm). Sodium diclofenac, used as a positive control, demonstrated potent activity with an IC₅₀ of 249.3 ppm. In the BSA model, overall inhibition values increased across all extracts, with n-hexane and ethanolic extracts showing enhanced activity, reaching 75.10% and 73.94% inhibition at 1000 ppm, respectively.  Ethanol extract demonstrated the strongest activity in the BSA model (IC₅₀ = 281 ppm), indicating that polar constituents contribute substantially to protein-stabilizing effects. While, ethyl acetate extract displayed moderate inhibition with an IC₅₀ of 697.6 ppm. The study highlights the importance of solvent selection and assay model in evaluating the bioactivity of kratom leaf extracts. Overall, kratom extracts possess measurable in vitro anti-inflammatory potential, though none surpassed the standard drug. Further phytochemical identification and in vivo studies are recommended to validate these activities.